Conservation and utilization of soft endosperm coconut accession from Andaman Islands - Jerard, B.A.; Damodaran, V.; Niral, V.; Samsudeen, K.; Rajesh, M.K.; Sankaran, M. (Journal of Plantation Crops, 2013)
The recent genetic resources explorations undertaken in Andaman Islands revealed the occurrence of coconut palms yielding soft endosperm among the natural coconut population called Thairu thengai or Nei thengai. The characterization of Thairu thengai accession from Andaman Islands using the in situ observations on seven palms revealed that the palms belong to tall group of coconut. The palms of this type bear fruits with both normal and soft endosperm. About 16 to 27 per cent of the fruits per bunch were observed to be with soft endosperm and the remaining ones were with normal firm endosperm. The normal nuts of the identified palms produced poor quality copra indicating some degree of softness. The soft endosperm fruits are of three types with difference in the layers of soft endosperm, nut water and firm endosperm. The palms are found to occur sporadically in South Andaman. Although these palms appear morphologically looking similar to other coconut palms except for endosperm trait, differences could be observed for many morphological and fruit component traits. The morphological and fruit component traits of Thairu thengai coconut are compared with the other other coconut populations. The strategies for conservation and utilization of this novel type of coconut are proposed.